Blackcurrant (Ribes nigrum L.) and Raspberry (Rubus idaeus L.) Ethanolic Extracts: Inhibitory Effects on Pancreatic Lipase and Antioxidant Activity - Rosa Tundis; Anna Rita Cappello; Monica Rosa Loizzo (Biology and Life Sciences Forum, 2023)
Blackcurrant (Ribes nigrum L.) and raspberry (Rubus idaeus L.) fruits, rich sources of phytochemicals such as polyphenols, have been shown to possess promising biological properties. Herein, both fruits from southern Italy have been extracted by maceration by using ethanol as the solvent and investigated for their potential pancreatic lipase inhibitory activity. The radical scavenging effects were also analysed by using the 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) tests. Our study showed that the extracts of both blackcurrant and raspberry have significant inhibitory activity against lipase with IC50 of 5.1 and 30.2 μg/mL, respectively, better than the positive control orlistat (IC50 of 37.1 μg/mL).